The epidural postoperative analgesia after a major urological procedures--a comparison of trimecaine and morphine to bupivacaine and fentanyl - Dostálová, Vlasta; Višňovský, Peter; Dostál, Pavel (Bratislavské lekárske listy, 2008)
OBJECTIVES: To compare the analgesic potency and side effects of epidural combination trimecaine with morphine and bupivacaine with fentanyl in postoperative analgesia after a major urological surgery. METHODS: We randomised 150 consecutive patients. In the trimecain/morphine group (n = 75) trimecaine 50 mg with 4 mg morphine was given epidurally in 8 hour intervals. In the bupivacain/fentanyl group (n = 75) the infusion of 0.25 % bupivacaine and fentanyl 2 microg/ml was administered at an infusion rate of 8 ml/h. RESULTS: The postoperative pain scores were lower in the trimecain/morphine group, the difference was significant during the first 6 hours after surgery, there was also a trend toward higher postoperative SpO2 values in this group, the difference was significant 36 hours after surgery. The total sum of postoperative complications and side effects was significantly higher in the bupivacian/fentanyl group (p = 0.002). CONCLUSION: The combination of epidural trimecaine with morphine after a major urological surgery provides a superior analgesia with fewer side effects when compared to epidurally delivered bupivacaine with fentanyl (Tab. 2, Fig. 5, Ref. 17). Full Text (Free, PDF) www.bmj.sk.
Keywords: anestetika lokální; bupivakain; trimekain; Pain, Postoperative; Analgesia, Epidural; Randomized Controlled Trials as Topic; Female; Pain Measurement; Morphine; Analgesics, Opioid; epidurální analgezie; Anesthetics, Local; fixní kombinace léků; ženské pohlaví; lidé; Fentanyl; urologické chirurgické výkony; Bupivacaine; měření bolesti; Trimecaine; Urologic Surgical Procedures; opioidní analgetika; Male; randomizované kontrolované studie jako téma; pooperační bolest; lidé středního věku; morfin; mužské pohlaví; fentanyl; Middle Aged; Drug Combinations; Humans